2011
DOI: 10.3917/pox.094.0007
|View full text |Cite
|
Sign up to set email alerts
|

La discrimination, de la qualification juridique à l'outil sociologique

Abstract: Résumé Cet article propose une réflexion théorique sur les enjeux de l’acclimatation de la notion de discrimination en sociologie, en prêtant une attention particulière aux rapports que cette catégorie entretient avec le droit. L’article plaide en faveur d’un usage contrôlé et réflexif de la notion de discrimination, pleinement attentif à l’usage que cette catégorie fortement marquée par le droit fait de l’analyse sociologique des rapports de pouvoir et des inégalités sociales. Après un retour sur le cadre jur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
16

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 0 publications
0
7
0
16
Order By: Relevance
“…Conflicts can arise when a ban on religion, sexual orientation, and sex discrimination is vindicated in the same company. French socio‐legal research has also shown the limits of the diversity paradigm in France and how social science can expose the challenges of the logic of anti‐discrimination law (Bereni and Chappe ).…”
Section: The American Construction Of the Anti‐discrimination Model mentioning
confidence: 99%
“…Conflicts can arise when a ban on religion, sexual orientation, and sex discrimination is vindicated in the same company. French socio‐legal research has also shown the limits of the diversity paradigm in France and how social science can expose the challenges of the logic of anti‐discrimination law (Bereni and Chappe ).…”
Section: The American Construction Of the Anti‐discrimination Model mentioning
confidence: 99%
“…Conflicts can arise when a ban on religion, sexual orientation, and sex discrimination is vindicated in the same company. French socio-legal research has also shown the limits of the diversity paradigm in France and how social science can expose the challenges of the logic of anti-discrimination law (Bereni and Chappe 2011).…”
Section: The Changing Nature Of Discrimination In the United States Amentioning
confidence: 99%
“…Mais si les normes juridiques de l'égalité hommes-femmes font consensus, la mise en oeuvre de cette égalité fait débat , ce qui donne lieu à une « égalité négociée » (Laufer, 2003). En matière de discrimination fondée notamment sur l'âge (Caradec et Poli, 2009), le sexe ou l'origine ethnique, les normes juridiques ont été pendant longtemps le seul outil de lutte (Ferre, 2004), à la mesure du saisissement tardif de ce sujet par la sociologie française (Bereni et Chappe, 2011). Depuis, les analyses des usages de ces normes, faiblement contraignantes pour les entreprises, ont montré la singularité du cas français par son acceptation d'une « diversité à la française » (Calvès, 2008 ;Rouland, 1994), alliant tradition juridique sur la notion d'égalité, héritage révolutionnaire et idéologie républicaine empreinte d'un « universalisme abstrait » (Wieviorka, 1996).…”
Section: Les Contraintes Législatives Et La Transformation Organisatiunclassified